How to adapt interventions to make them culturally relevant: cultural modification and adaptation of escape-pain programme for Malaysian context - Che Hasan, Muhammad Kamil (2019)
Aim: To provide delegates with information and practical skills in how to use psychological techniques for optimal engagement among older people in fall prevention interventions.